One-step preparation of chitosan/sodium dodecyl sulfate-stabilized oil-in-water emulsion of Zingiber cassumunar Roxb. oil extract - Panya Sunintaboon (2018)
Chitosan/sodium dodecyl sulfate (CS/SDS)-stabilized emulsions of oil extract from Zingiber cassumunar Roxb. or plai oil were prepared in a one-step emulsification process. The effects of CS, SDS, and plai oil amounts on average droplet size, CS/SDS adsorption and colloidal stability of resulting emulsions were investigated using laser light scattering and zeta potential measurements, Fourier transform infrared (FTIR) spectroscopy, and transmission electron microscopy (TEM). Emulsion stability, loading capacity, and emulsification efficiency were also determined. This one-step approach of involving positively charged CS macromolecules associated with negatively charged surfactant molecules, SDS, as an emulsifying system for micronic and submicronic oil-in-water emulsions brought new scientific insights about interfacial adsorption of polymer/surfactant complexes and the interplay between bulk solution behavior and emulsion fabrication and stability. © 2012 Elsevier B.V.